4th International Symposium on High-Temperature Metallurgical Processing : proceedings of a symposium sponsored by the Pyrometallurgy Committee and the Energy Committee of the Extraction and Processing Division of TMS (The Minerals, Metals & Materials Society) : held during the TMS 2013 Annual Meeting & Exhibition, San Antonio, Texas, USA, March 3-7, 2013 - International Symposium on High-Temperature Metallurgical Processing 2013 : San Antonio, Tex.); Jiang, Tao.; Minerals, Metals and Materials Society; Metallurgical Society (U.S.). Annual Meeting (2013 : San Antonio, Tex.) (Hoboken, N.J. : Wiley, 2013)
"Nine topics are covered in this book: High Efficiency New Metallurgical Technology, Fundamental Research of Metallurgical Process, Alloy and Materials Preparation I, Alloy and Materials Preparation II, Roasting, Reduction, and Smelting, Simulation and Modeling, Treatment and Recycling of Solid Slag/Wastes, Energy and Environment."--
Includes bibliographical references and index.
Keywords: Metallurgy -- Congresses; TECHNOLOGY & ENGINEERING -- Material Science; Metallurgy; Electronic books; Conference papers and proceedings